High-dose methylprednisolone in the treatment of active ulcerative colitis. - Rosenberg, W; Ireland, A; Jewell, D (1990)
Twenty patients with severe active ulcerative colitis were entered into a pilot study to test the efficacy of pulsed high-dose methylprednisolone in inducing remission. Of 20 patients, 12 improved, but 8 of 20 patients (40%) who did not went for urgent colectomy. The group proceeding to surgery tended to have more extensive disease. These results contrast unfavorably with historical control data from this unit.